DISCOURSE ANALYSIS OF THE REGENT PROMISES IN CAMPAIGN - Kadir, Anisa Abdul; Latif, Taib; Octasary, Magvirah; Lestari, Sri Ayu Budi; Yetty, Yetty (Cakrawala Bahasa, 2025)
This study aimed to determine what political promises have been realized and have not been realized in the economic prosperity by the Regent and Deputy Regent of West Halmahera. This research used the correspondence theory of truth, meaning that researchers want to know whether the promises have been realized can be utilized and felt by the community. This research used descriptive qualitative methods, with data collection techniques are observation, interviews and documentation. The informants were 2 fish traders, 1 groceries trader, 1 clothing trader, 1 Head of BLK and 1 BLK participant who were interviewed. The results of this study indicate that there are 8 promises offered in the economic prosperity during the campaign, but until 3 years have served as Regent of West Halmahera only 2 promises have been realized and 6 promises have not been fully realized in the economic prosperity, namely market improvements and re-functioning the Work Training Center (BLK) building.